Synthesis and thermal properties of difunctional polysulfone telechelics - Torun, Lokman (SPRINGER, 2017)
Three series of dichloride and dihydroxyl-terminated polysulfone telechelics (Cl-PES-Cl and HO-PES-OH, M (n) = 2580-12,750 daltons) were prepared from bis(4-chlorophenyl) sulfone with bisphenol A, 4,4'-dihydroxydiphenyl ether and 4,4'-dihydroxybiphenyl. The glass transition temperatures and thermal stabilities of the 30 telechelics synthesized were evaluated as a function of molecular weights and the nature of the end groups. It was observed that the glass transition temperatures of lower molecular weighted dihydroxyl telechelics are higher, due to the capabilities of forming hydrogen bonds, than the corresponding dichloride telechelics. On the other hand, the increase in the glass transition temperatures was steeper with dichloride-terminated oligomers as compared to the corresponding dihydroxyl-terminated ones. In addition, dichloride telechelics manifest higher thermal stabilities than dihydroxyl-terminated oligomers.
Keywords: Polysulfone; Polysulfone oligomers; Polysulfone macromonomers; Polysulfone telechelics; Glass transition temperatures; Hydrogen bonding; Thermal stability; POLY(ARYLENE ETHER SULFONE); PROTON-EXCHANGE MEMBRANES; AMPHIPHILIC GRAFT-COPOLYMERS; CLICK CHEMISTRY; ULTRAFILTRATION MEMBRANES; MULTIBLOCK COPOLYMERS; POLY(ETHER SULFONE); PROTEIN ADSORPTION; END-GROUPS; POLYMERIZATION; Polymer Science